2024
DOI: 10.1186/s42269-023-01161-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of tumor growth regression of quinoa and chia oil nanocapsules via the control of PIK3CA and MYC expression, anti-inflammation and cell proliferation inhibition, and their hepatorenal safety in rat breast cancer model

Aida I. El makawy,
Sekena H. Abdel-Aziem,
Shaimaa E. Mohammed
et al.

Abstract: Background The second most common cancer in the world is breast cancer. Chemotherapy is used to treat breast cancer, but instances of multidrug resistance, targets that are not selective, and physicochemical issues raise doubts about its efficacy. So, the exploration of chemopreventive agents from efficient natural sources has been required. The chia and quinoa seeds have health-promoting activities that include cardio-protective, antidiabetic, and anticancer effects. Given the paramount import… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Studies have reported important health benefits associated with quinoa consumption, including anti-inflammatory, antioxidant, anticancer, antihypertensive, hypo-cholesterolemic, prebiotic, and antidiabetic properties [11][12][13][14][15][16][17]. These benefits are attributed to bioactive compounds such as polyphenols, flavonoids, phytosterols, essential fatty acids, and dietary fiber [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported important health benefits associated with quinoa consumption, including anti-inflammatory, antioxidant, anticancer, antihypertensive, hypo-cholesterolemic, prebiotic, and antidiabetic properties [11][12][13][14][15][16][17]. These benefits are attributed to bioactive compounds such as polyphenols, flavonoids, phytosterols, essential fatty acids, and dietary fiber [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%